PENGEMBANGAN MEDIA TIRAI SAINS BERBASIS MODEL ROLE PLAYING PADA PELAJARAN IPA DI SD NEGERI 5 SRIKATON - Lisa Luviana; Harmoko Harmoko; Tri Juli Hajani (Jurnal Perspektif Pendidikan, 2022)
This study aims to develop a Science Curtain Media Based on Role playing Models in Science Learning at State Elementary School 5 Srikaton which is valid and practical. This type of research is research and development (R&D) using the ADDIE development model which consists of 5 stages, namely: analysis stage, design stage, development, implementation, and evaluation. Data collection techniques using interviews and questionnaires. The instrument used in the research on Science Curtain Media Based on Role playing Models in Elementary School Science Learning is a questionnaire for the assessment of linguists, material experts, and media experts. Meanwhile, for the practicality of Science Curtain Media Based on Role playing Models in Elementary School Science Learning using student and teacher respondent questionnaires. Overall, the value of the analysis and calculation of the value of the questionnaire sheet from the expert team of science curtain learning media based on the role playing model belongs to the very valid category with a percentage of 93% meaning that the science curtain learning media based on the role playing model is valid. Based on the percentage of the overall value from the analysis of the practicality test questionnaire sheet, the science curtain learning media based on the role playing model belongs to the very practical category with a percentage of 95.8%, meaning that the science curtain learning media based on the role playing model that has been developed is very practical to use.